Native Plants That Benefit Native Wildlife in the Florida Panhandle - Holly K. Ober; Gary W. Knox (EDIS)
The key to enhancing wildlife (and attracting it to your property) is to provide the resources wildlife need. This means supplying food, water, and cover within the space you own and manage. Because the needs of each wildlife species for food and cover vary from one season to the next, a mix of plant species is required to meet the needs of a species all year round. And because each species has different needs, attracting and maintaining a wide variety of wildlife year round requires a wide diversity of plants. A property owner interested in attracting wildlife should nurture a wide variety of native plants to ensure that there is a large assortment of food and cover options available all the time. This 8-page fact sheet was written by Holly K. Ober and Gary W. Knox, and published by the UF Department of Wildlife Ecology and Conservation, October 2013.